2016
DOI: 10.3389/fnhum.2016.00149
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Methylphenidate on Resting-State Functional Connectivity of the Basal Nucleus of Meynert, Locus Coeruleus, and Ventral Tegmental Area in Healthy Adults

Abstract: Background: Methylphenidate (MPH) influences catecholaminergic signaling. Extant work examined the effects of MPH on the neural circuits of attention and cognitive control, but few studies have investigated the effect of MPH on the brain's resting-state functional connectivity (rsFC).Methods: In this observational study, we compared rsFC of a group of 24 healthy adults who were administered an oral 45 mg dose of MPH with a group of 24 age and gender matched controls who did not receive MPH. We focused on three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 169 publications
(199 reference statements)
1
31
0
Order By: Relevance
“…Previous functional studies on the LC have exclusively been done using 1E-fMRI and frequently use the Keren 2 SD atlas. Across those studies, regions that typically emerge in iFC analyses are the prefrontal cortex, cerebellum, right supplementary motor area, cingulate cortex, thalamus, visual cortex, lingual and fusiform gyrus, insula, amygdala, and the hippocampus (e.g., Bär et al, 2016;Köhler, Wagner, & Bär, 2016;Kline et al, 2016;Murphy et al, 2014;Sterpenich et al, 2006). Nearly all these regions were ranked highly across the 1E…”
Section: Functional Connectivity Of the Lc In Typical Young Adultsmentioning
confidence: 99%
“…Previous functional studies on the LC have exclusively been done using 1E-fMRI and frequently use the Keren 2 SD atlas. Across those studies, regions that typically emerge in iFC analyses are the prefrontal cortex, cerebellum, right supplementary motor area, cingulate cortex, thalamus, visual cortex, lingual and fusiform gyrus, insula, amygdala, and the hippocampus (e.g., Bär et al, 2016;Köhler, Wagner, & Bär, 2016;Kline et al, 2016;Murphy et al, 2014;Sterpenich et al, 2006). Nearly all these regions were ranked highly across the 1E…”
Section: Functional Connectivity Of the Lc In Typical Young Adultsmentioning
confidence: 99%
“…Recent human fMRI studies revealed the baseline functional connectivity of the LC (Murphy, O'Connell, O'Sullivan, Robertson, & Balsters, ; Jacobs, Müller‐Ehrenberg, Priovoulos, & Roebroeck, ; Wagner et al, ; Zhang, Hu, Chao, & Li, ). Furthermore, fc changes provoked by medication (Kline et al, ; Liebe et al, ; Song et al, ; Wagner, de la Cruz, Köhler, & Bär, ) and differences of the connectivity in Alzheimer's disease were found (Serra et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…First, human PET studies have shown that at clinical doses (such as those used herein), MPH binds to the NET with a higher affinity than to the DAT [12,13]. Second, there is further evidence from studies in experimental animal showing that MPH can directly affect the discharge properties of the locus coeruleus (LC) [54], which is the main source of noradrenergic innervation in the brain; these findings are supported by a rs-fMRI study in humans showing that MPH exerts effects on the FC of the LC [55]. Third, there is a general consensus that the MPH procognitive effects in ADHD patients and HC involve modulation of the prefrontal cortex (PFC) [56].…”
Section: Discussionmentioning
confidence: 64%